URGENSI KAIDAH FIKIH DAN APLIKASINYA TERHADAP MASALAH-MASALAH SOSIAL - Abnan Pancasilawati (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
There is an urgency of fiqih norms and its application to solve social problems. Fiqih norms is a part of fiqih study and becomes one of the methods in Islamic law. Without understanding of fiqih norms, someone’s understanding about Islamic law will be not comprehensive, because it can make the law practitioners easy to understand the problems related to fiqih. The position of fiqih norms as a complementary subject after Al-Qur’an and Sunnah has been a convention among Moslems. In other sides, the position of fiqih norms as a source is still debatable among Moslems. It is because fiqih norms tend to have an unknown exception for some Moslems. In this case, some ulama use fiqih norms which are based on the nash to determine a regulation which it has not established yet.